+Chlorination by-products in indoor swimming pools: Development of a pilot pool unit and impact of operating parameters. (April 2020) - Tsamba, Lucie; Correc, Olivier; Couzinet, Anthony
Highlights: Assessment of an innovative pilot pool plant, aiming at studying DBP formation. DBP levels in the pilot plant are representative of French indoor swimming pools. Correlations are established between operating parameters and DBP levels. Abstract: Chlorine addition in swimming pools ensures the microbiological quality of the water and the bathers' safety. However, water chlorination is associated with disinfection byproducts (DBP) formation and adverse health effects. The impact of operating parameters and innovative water treatment systems on DBPs levels has been reported in several studies, but sampling campaign in real pools remain difficult to carry out, mainly due to unexpected attendance variations. This study presents the development of a pilot pool plant allowing to perform experiments under controlled and reproducible conditions. Bathers inputs were simulated both for the organic load and for the mechanical agitation of water. Two sampling campaigns were performed during the building of the pilot, before and after the hall was closed. Key operating parameters such as chlorine dose, water temperature and attendance were controlled and monitored. DBP levels in the pilot plant were representative of French indoor swimming pools and the impact of bathers' activity was visible on volatile DBPs. Furthermore, correlations could be stated between operating parameters and DBP levels. Stripping effectively reduced volatile DBP concentrations in water. Moreover, energy consumption data, which are usually very scarce in experimental studies, showed the influence of heat pump consumption on the global energy consumption.